Improved Black Silicon for Photovoltaic Applications. Issue 8 (12th April 2013) - Algasinger, Michael; Paye, Julie; Werner, Florian; Schmidt, Jan; Brandt, Martin S.; Stutzmann, Martin; Koynov, Svetoslav
Abstract The morphology and the electronic properties of monocrystalline Si (c‐Si) with a nano‐textured "black" surface, obtained by a metal‐catalyzed wet etching process, and the improvement by an additional chemical treatment are examined with regard to solar cell applications. Photoluminescence and optical reflectivity measurements show the presence of a nano‐porous Si (np‐Si) phase in the as‐prepared nano‐texture. It is found that an additional wet chemical treatment with the standard clean 1 of the common RCA cleaning process removes the np‐Si fraction and significantly alters the surface of the nano‐structure. Cross‐sectional scanning electron microscopy images reveal a pronounced reduction of the surface area, to values of only 3–6 times that of a planar surface. Electron spin resonance measurements were performed to investigate the type and quantity of defects induced by the nano‐texturing process. The optimized nano‐texture exhibits a Si dangling bond density comparable to planar c‐Si wafers. Electrically detected magnetic resonance spectra reveal an additional paramagnetic defect present in the nano‐textured Si, linked to a hydrogen‐ or oxygen‐related double donor. In addition, initial results on the passivation of surface defects via atomic layer deposition of Al2O3 are presented. Photoconductance decay measurements of passivated samples show a tenfold increase of the effective lifetime for nano‐textures which have received the additional etching treatment. The improved electronic quality of the nano‐textured surface makes it an interesting candidate for application as an anti‐reflection surface in solar cells.